Strategic Scientific Workshop “Co-production of knowledge in climate governance” - Hayden, Juliana; Lohse, Eva Julia; Porrone, Arianna; Poto, Margherita Paola (Septentrio Reports, 2022)
The overall aim of this report is to record the research objectives, results to date, and points for further investigation regarding knowledge co-production in climate governance. The aim is to continue the conversation initiated at the Scientific Strategic Workshop “Co-production of knowledge in climate governance”, held at the University of Bayreuth Center of International Excellence "Alexander von Humboldt", on May 5–6, 2022.